A Study On The Teaching Learning Process Of Reading In English Department Of Muhammadiyah University Of Surakarta: AMicro Ethnography - Purwaningsih, Handayani (2012)
English department of Muhammadiyah University of Surakarta. The research was conducted in reading IV class at English department of Muhammadiyah University of Surakarta in 2012/2013. It focuses on the learning objective, syllabus, methods, materials, classroom techniques, procedure, teacher role, student role, media, the strength, and weakness in reading class. The subjects of the study are the teachers in reading class (Mr.Spl at class B and Mrs.RF at class H) of Muhammadiyah University of Surakarta in the fourth semester 2011/ 2012 academic year. The object of the study is teaching learning process of reading at English Department of Muhammadiyah University of Surakarta in fourth semester 2011/ 2012 academic year. There are three sources of the data; event, informant, and document. The data were collected through observation, interview, and document. The technique of analyzing data is an interactive model that includes three main components, namely the reduction of data, the display of data and conclusion or verification. The results of the research are (1) the learning objectives are dived into two kinds; (a) the general objectives are to become better reader, to activate and reinforce other skills, to activate and reinforce other skills, and to develop critical thinking skills. (b) the specific objectives are to prepare students to do reading test of TOEFL and IELTS; and also to help students to communicate with other in every situation outside the class. (2)The syllabus used is skill- based syllabusthat contain group linguistic competencies (pronunciation, vocabulary, grammar, and discourse). (3)The materials are authentic materials and printed material. (4)The method used is Eclectic Method, which combines three methods, namely; Grammar- Translation Method (GTM), Direct Method (DM), and Communicative Language Teaching (CLT). There are three steps of teaching reading namely: the opening, study session, and closing. (5)The teachers procedures are: (a) Pre-reading, (b) While-reading (c) Post-reading, (6)The technique is reading aloud. (7) The media is just a copy of reading text. (8) The teachers roles are (1) as a counselor (2) as a guide (3) as an. (9) The student's roles are as active participate. (10) The strengths are seen from the objective of reading IV, the syllabus, the method, the materials. The weaknesses are seen from the media and the technique in reading IV class The writer found that the teaching learning process of reading at English department of Muhammadiyah University of Surakarta is teaching learning of reading. It made the students actively participate in the teaching learning process.